Village stay reservation and management system for local tourism industry / Abidah Mat Taib... [et al.] - Mat Taib, Abidah; Zainuddin, Nur Athirah; Haron, Noorazalia Izha; Ahmad Zukri, Nurul Hidayah (UiTM Cawangan Perlis, 2020)
Tourism industry in Malaysia is being developed to be better thus, making Malaysia as one of the most attractive countries to visit. Many Village Stays in Malaysia are owned and managed by inexperienced personnel and have in efficient system. Therefore, local products and nearby tourist attractions are unable to be properly advertised or are not made known to the public. So, the objectives of this project are to develop Village Stay Reservation and Management System that caters for the information of the local tourist attraction products and to evaluate Village Stay Reservation and Management System in terms of perceived ease of use. In order to achieve the objectives, this project developed the system using PHP programming language and tested the functionality, usability and user acceptance of the system. Fifteen respondents were involved in the testing of this system. A set of questionnaires was used to collect the data. The mean for user acceptance test is 3.77 while for user reaction in usability testing is 3.74. The respondents are satisfied with the system in terms of its usability. Inconclusion, this research has achieved the objectives. It is shown that the users can deal more effectively and efficiently when using this system. This system will reduce the workload of the staffs when using an online system to monitor the reservation as well as attending to other chores.